Reworking songs past and present: literary forms and traditions in Chinese court drama - Tan, TY (Nanyang Technological University, 2023)
Ming and Qing dynasty court plays are commonly read and used as valuable sources for understanding the court performance traditions and practices in late imperial China. As such, however, they are largely studied as a separate field of research in theater history, in isolation from other Chinese literary genres. To redress the imbalance in current scholarship, this paper reconsiders the role and place of court drama in Chinese literary history and calls attention to the potential interconnections between court drama and other forms of Chinese literatures. The paper proposes a new approach to link court drama to Chinese literary tradition by focusing on the composite nature of court drama texts. Using the Qing dynasty court play Bayi wu Yuting as a case study, it explores ways of reading court drama as a composite literary text consisting of various poetic genres and components deriving from different historical periods and engaging actively with these literary traditions.